(untitled) (Contemporary Mathematics, 2020)
In this article, we give some improvements and generalizations of the famous Jensen’s and Jensen-Mercer inequalities for twice differentiable functions, where convexity property of the target function is not assumed in advance. They represent a refinement of these inequalities in the case of convex/concave functions with numerous applications in Theory of Means and Probability and Statistics.